Waste minimization benefits and obstacle for solid industrial waste in Malaysia - Mallak, Shadi Kafi; Ishak, Mohd Bakri; Mohamed, Ahmad Fariz (International Organization of Scientific Research, 2014)
Moving toward a sustainable industrial activity requires an effective waste management that is applicable and efficient for all different types of industrial wastes .Waste minimization as the most acceptable option in waste management hierarchy, has a significant contribution in minimizing the solid wastes generated by manufacturing industries. The absence of appropriate policy, lack of awareness and information ,inadequate guidelines , limited time , lack of cooperation and application of old technologies such as end of pipe approaches are the common obstructive factors towards practicing efficient waste minimization by industries. The study was conducted to review and analyze the practical waste minimization methodologies and its characteristics based on the industrial activities. In addition the obstacles which hold up industries from practicing waste minimization efficiently were determined. Thus this study suggest the effective practices for improving waste minimization which suitable for manufacturing industries in Malaysia.